Tandem Solar Cells: Vacuum‐Assisted Growth of Low‐Bandgap Thin Films (FA0.8MA0.2Sn0.5Pb0.5I3) for All‐Perovskite Tandem Solar Cells (Adv. Energy Mater. 5/2020). Issue 5 (3rd February 2020) - Abdollahi Nejand, Bahram; Hossain, Ihteaz M.; Jakoby, Marius; Moghadamzadeh, Somayeh; Abzieher, Tobias; Gharibzadeh, Saba; Schwenzer, Jonas A.; Nazari, Pariya; Schackmar, Fabian; Hauschild, Dirk; Weinhardt, Lothar; Lemmer, Uli; et al.
Abstract : Efficient vacuum‐assisted growth control (VAGC) allows growing micron‐sized and pinhole‐free low bandgap ( E G ≈ 1.27 eV) perovskite thin‐films for fabrication of efficient low‐bandgap perovskite solar cells. This efficient low‐bandgap perovskite solar cells enable achieving efficient all‐perovskite tandem solar cells. VAGC exhibits promising reproducibility and potential in larger active‐area solar cells up to 1 cm 2 . More details can be found in article number 1902583 by Bahram Abdollahi Nejand, Ulrich W. Paetzold, and co‐workers.